Better together: nanoscale co-delivery systems of therapeutic agents for high-performance cancer therapy - Sun, Liyan; Li, Zhe; Lan, Jinshuai; Wu, Ya; Zhang, Tong; Ding, Yue (Frontiers in Pharmacology, 2024)
Combination therapies can enhance the sensitivity of cancer to drugs, lower drug dose and reduce side effects in cancer treatment. However, differences in physicochemical properties and pharmacokinetics of different therapeutic agents limit its application.To avoid the above dilemma and achieve accurate control of the synergetic ratio, nanoscale co-delivery system (NCDS) has sprung up as a prospective tool for combined therapy in cancer treatment, which is increasingly being used to co-load different therapeutic agents. Here, we have summarized the mechanisms of therapeutic agents in combination for cancer therapy, nanoscale carriers for co-delivery, drug-loading strategies and controlled/targeted co-delivery systems, aiming to give a general picture of these powerful approaches for future NCDS researches.